The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.32350/bsr.0102.03
|View full text |Cite
|
Sign up to set email alerts
|

Development and Optimization of MicroPropagation, In Vitro Methodology for Gladiolus

Abstract: Gladiolus is a non-native, costly but an important flowering plant in South Asia. Considering its lower production rate and economic importance, micro-propagation technology was optimized in this study to establish a protocol for pathogen free clonal genotypes. Taken the results together, the best response was observed at 27°C as growing temperature, table sugar (sucrose) as a carbon source, apical Keywords BAP IBA Kinetin Micro-propagation MS basal medium NAA meristem of 3mm for shoot formation as an explant.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…Some research reports, however, suggested lower BAP concentrations for shoot regeneration; one such report [94] found that 0.5 mg L-1 BA produced the best results, while [81] obtained better results at concentrations of BAP in the range of 0.5 to 1.0 mg L −1 . Furthermore, increasing BAP concentration from 0.5 to 1.0 mg L −1 increased shooting, while further increases resulted in a low rate of shoot development [80]. Several researchers have reported on NAA alone and its positive influence on in vitro growth [31,54,62,63], as well as in combination with other PGRs, as also reported by [28].…”
Section: Effect Of Plant Growth Regulatorsmentioning
confidence: 63%
See 2 more Smart Citations
“…Some research reports, however, suggested lower BAP concentrations for shoot regeneration; one such report [94] found that 0.5 mg L-1 BA produced the best results, while [81] obtained better results at concentrations of BAP in the range of 0.5 to 1.0 mg L −1 . Furthermore, increasing BAP concentration from 0.5 to 1.0 mg L −1 increased shooting, while further increases resulted in a low rate of shoot development [80]. Several researchers have reported on NAA alone and its positive influence on in vitro growth [31,54,62,63], as well as in combination with other PGRs, as also reported by [28].…”
Section: Effect Of Plant Growth Regulatorsmentioning
confidence: 63%
“…The surface sterilization of explants was accomplished using a variety of procedures, which differed based on the species of gladiolus and the type of explant. Explants of gladiolus were cleaned with detergents like Teepol, Tween 20, liquid detergent, or savlon, then exposed to sodium hypochlorite (NaOCl) as reported in various works [28,59,79,80]. Numerous research reports also advise applying clorox centramide, dithane M-45, bavistin, antiseptic savlon, dematos with alcohol, and other primary sterilants like HgCl 2 and NaOCl [11,23,35,53,64,66,[81][82][83].…”
Section: Mother Plant Sanitation Conditions and Sterilization Of Expl...mentioning
confidence: 99%
See 1 more Smart Citation
“…The sprouted cormlets treated with R 4 took minimum (8.31) days for in-vitro root initiation, which was statistically at par with R 8 (8.61 days), R 7 (8.66 days) and R 5 required the maximum days (10.78 days). The minimum time of root induction (7.2 days) with maximum rooting (96%) was observed with 1.0 mg/L of IBA [15]. Similarly, R 4 produced the maximum number of roots/shoot (5.37) at 30 days after inoculation, which was statistically at par with R 6 (5.34) and R 7 developed the minimum number of roots/shoot (3.65) (Table 2).…”
Section: Resultsmentioning
confidence: 84%
“…Silva et al [14] found that the regeneration of gladiolus from dormant cormlets suggested the fact regarding breaking of dormancy through hormonal action followed by consequent supply of readily available nutrients suitable to growing tissues from the medium. Induction of shoot bud within 7-8 days 16 and 7.8 days with maximum shooting (96%) [15] was observed in B5 (Gamborg) and MS medium respectively when it was supplemented with 1.0mg/L of BAP. Similar kind of findings was also reported by Budiarto [16] and [17].…”
Section: Resultsmentioning
confidence: 97%